Deductive Logic as a Critical Thinking Technique for Islamic Religious Education Students - Firdausy Nuzula; Rafif Danu Pramatya; Ahmad Fathur Rizqi Jalil; Moh. Faizin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Deductive logic plays an important role in developing a student's critical thinking skills, especially Islamic Religious Education students. A student can use the deduction process to draw valid conclusions based on premises that have been accepted as true. In Islamic religious education, this ability is very necessary in analyzing and understanding religious concepts that require in-depth understanding, such as interpretation of the Koran, Hadith, and so on. Through deductive logic, students can develop a critical nature towards the many interpretations of existing religious teachings, and are able to differentiate between various points of view based on rationalism and dogmaticism. A mature abstraction of thought accompanied by the use of a deductive approach will help students build coherent and structured arguments in addressing contemporary issues related to the Islamic religion. Therefore, mastering the logic of deduction not only improves students' critical thinking skills, but also enriches their perspective in understanding and applying Islamic teachings in everyday life.